2017
DOI: 10.1016/j.ajhg.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Signaling Adaptor LAT Contributes to the Neuroanatomical Phenotype of 16p11.2 BP2-BP3 CNVs

Abstract: Copy-number changes in 16p11.2 contribute significantly to neuropsychiatric traits. Besides the 600 kb BP4-BP5 CNV found in 0.5%-1% of individuals with autism spectrum disorders and schizophrenia and whose rearrangement causes reciprocal defects in head size and body weight, a second distal 220 kb BP2-BP3 CNV is likewise a potent driver of neuropsychiatric, anatomical, and metabolic pathologies. These two CNVs are engaged in complex reciprocal chromatin looping, intimating a functional relationship between gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…The human 16p11.2 chromosomal region is a hotspot of recurrent pathogenic copy number variants with diverse sizes, breakpoints, and gene content. Most breakpoints map within homologous segmental duplication clusters, consistent with non-allelic homologous recombination (NAHR) (Loviglio et al 2017). Among these variants, 600 kbp deletions and duplications with breakpoints BP4 and BP5 are among the most frequent genetic causes of neurodevelopmental and psychiatric disorders (Weiss et al 2008;McCarthy et al 2009;Zufferey et al 2012;D'Angelo et al 2016;Marshall et al 2017).…”
Section: Introductionmentioning
confidence: 84%
“…The human 16p11.2 chromosomal region is a hotspot of recurrent pathogenic copy number variants with diverse sizes, breakpoints, and gene content. Most breakpoints map within homologous segmental duplication clusters, consistent with non-allelic homologous recombination (NAHR) (Loviglio et al 2017). Among these variants, 600 kbp deletions and duplications with breakpoints BP4 and BP5 are among the most frequent genetic causes of neurodevelopmental and psychiatric disorders (Weiss et al 2008;McCarthy et al 2009;Zufferey et al 2012;D'Angelo et al 2016;Marshall et al 2017).…”
Section: Introductionmentioning
confidence: 84%
“…The linker for activation of T cells (LAT) is a membrane adaptor protein involved in T cell receptor‐mediated signaling and essential for T cell development and activation . It has been recently shown that LAT also plays an important role in neurogenesis, and it contributes to neurodevelopmental phenotypes associated with 16p11.2 CNVs . Taken together, these findings provide a good example of the potential link between immunological disturbances and alterations in vocalization.…”
Section: Common Traits Between Immunity and Vocalizationmentioning
confidence: 92%
“…Other studies demonstrate that in mouse models, Kctd13 epistatically affects anatomical phenotypes in combination with Mvp (major vault protein) or Lat (linker for activation of T cells) , genes, which are also located in 16p11.2 loci. However, recent studies reported no robust abnormalities in brain structure of mice with genetic ablation of Kctd13 , and instead observed sex‐specific differences in brain volume of double heterozygous mice lacking one copy of Kctd13 and one copy of either Lat or Mvp , also located in 16p11.2 .…”
Section: Kctd Genes Associated With Neurodevelopmental and Neuropsychmentioning
confidence: 99%